Digitalization of Public Sector AIS in Indonesia: Opportunities and Challenges (A Systematic Literature Review) - Abdul Razik Luneto; Rika Febby Rhamadhani; Annastry Widyakusuma; Rizkiani Iskandar (Majalah Bisnis & IPTEK, 2025)
This research systematically investigates the effective implementation of digital transformation in the public sector, with a focus on the renewal of Accounting Information Systems (AIS) as a key component. Employing a Systematic Literature Review (SLR) approach based on the PRISMA framework, the study identified, selected, and analyzed 39 relevant articles sourced from the Scopus database. The analysis centers on implementation, contributing factors, challenges, and opportunities, with a specific focus on the Indonesian context. The findings indicate that digital transformation is a fundamental paradigm shift from simply E-Government towards a more holistic and collaborative Government as a Platform (GaaP) model. The success of implementation is contingent upon factors like robust political leadership, a cohesive policy framework, and multi-stakeholder collaboration. On the other hand, the process is frequently impeded by significant hurdles, such as bureaucratic fragmentation, sectoral protectionism, outdated legacy systems and a skills gap in digital literacy among public officials. While these challenges are acute in Indonesia, they are offset by strategic opportunities to achieve technological leapfrogging and scale up successful local initiatives nationwide. This research concludes that AIS transformation is not the goal, but a pivotal enabler for the successful digital transformation of the entire public sector.